2018
DOI: 10.1016/j.neurobiolaging.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Novel lactopeptides in fermented dairy products improve memory function and cognitive decline

Abstract: Alongside the rapid growth in aging populations, prevention of age-related memory decline and dementia has become a high priority. Several epidemiological and clinical studies have concluded that fermented dairy products can help to prevent cognitive decline; furthermore, intake of Camembert cheese prevents Alzheimer's pathology in model mice. To elucidate molecular mechanisms underlying the preventive effects of fermented dairy products, here we screened peptides from digested fermented dairy products for abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 19 publications
5
100
0
1
Order By: Relevance
“…Accumulating studies indicate that fermented dairy products rich in ␤-lactolin improve cogni- tive performance and dementia [15,17]. However, the effects of ␤-lactolin on AD pathologies and cognitive decline have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating studies indicate that fermented dairy products rich in ␤-lactolin improve cogni- tive performance and dementia [15,17]. However, the effects of ␤-lactolin on AD pathologies and cognitive decline have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that ␤lactolin orally administered can enter the brain and inhibit the activity of monoamine oxidase B (MAO-B), thereby resulting in increased dopamine levels in the brain in normal ICR mice [15,21], and dopamine D1-like receptor is involved in the memory improvement induced by ␤-lactolin in scopolamine-induced amnesia model mice [15]. In the present study, the levels of dopamine in the frontal cortex increased in 5 × FAD mice fed with the diet containing ␤-lactolin and whey digestion rich in ␤-lactolin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MKP, a tripeptide with greater blood-brain barrier (BBB) penetration, was one of the primary players in the prevention of cognitive impairment (Table 1). On the other hand, from milk whey digestion products, GTWY peptides in the b-lactoglobulin sequence were identified as the components responsible for improving memory function in a scopolamine-induced amnesia mouse model (Ano et al, 2018; Table 1). The underlying mechanism was probably inhibition of the monoamine oxidase-B activity and subsequent increment in dopamine levels in the brain.…”
Section: Cognitive Decline: Risk and Protective Factorsmentioning
confidence: 99%
“…Previous studies indicate that some dipeptides improve memory, ameliorate depression, and relieve anxiety. For example, a pyroglutamyl-leucine dipeptide exerts antidepressant effects (7), a tyrosine-leucine dipeptide acts as an anxiolytic agent with activity comparable with that of diazepam (8), and a tryptophan-tyrosine dipeptide ameliorates deficiencies in memory (9,10). Further, an epidemiological study found that consumption of low-fat dairy products, including fermented products, is inversely associated with the symptoms of depression (11,12).…”
mentioning
confidence: 99%